Systemic Lupus Erythematosus: Initial Manifestation as Cardiac Tamponade? - Zechen Ma; Xiaoyang Lan; Kevin R. Bainey (Annals of Internal Medicine: Clinical Cases)
A 49-year-old man presented with 1 hour of retrosternal chest pain and ST-segment elevation. In the ambulance, he was diagnosed with an ST-segment elevation myocardial infarction and received prompt fibrinolysis. On arrival to the percutaneous coronary intervention–capable hospital, he became hemodynamically unstable, and bedside echocardiogram demonstrated a posterior pericardial effusion with tamponade physiology. He was found be profoundly thrombocytopenic secondary to a history of immune thrombocytopenic purpura (not known at the time of prehospital fibrinolysis). Given the position of his pericardial effusion, emergent surgical drainage was performed without complication. Subsequent work-up confirmed effusive pericarditis as his presenting diagnosis secondary to systemic lupus erythematosus.